Inspirational Leadership in Encouraging Academic Achievement in Vocational High Schools - Widodo, Cahyo; Sukatiman, Sukatiman; Isnantyo, Fajar Danur (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study explores the role of inspirational leadership, often identified with transformational leadership, in enhancing academic achievement within vocational high schools. Using a Systematic Literature Review (SLR) approach with PRISMA methodology, the research synthesizes findings from 40 articles published between 2018 and 2024. The PRISMA approach is utilized for analysis. Data in systematic reviews that aim to screen, evaluate, and transparently report literature. The steps of data analysis with PRISMA involve a process of identification, screening, eligibility assessment, and inclusion of relevant literature. The analysis highlights the capacity of transformational leadership to foster collaboration, innovation, and motivation among school stakeholders. It underscores the influence of leadership in integrating entrepreneurial values, developing innovative teaching methods, and creating an inclusive school culture. The study also identifies a significant research gap in understanding the direct application of transformational leadership in vocational contexts. Recommendations are made for school leaders to implement transformational leadership practices aligned with contemporary educational challenges, focusing on equipping students with both academic and practical skills for the workforce.